Accordion-shaped MBene material and preparation method thereof

By mixing MoAlB with NaOH solution and subjecting hydrothermal treatment to form an accordion-shaped MBene material, the problem of limited specific surface area of ​​the existing MBene material is solved, and the performance and application efficiency of the material are significantly improved.

CN119873851APending Publication Date: 2025-04-25CHANGAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510070729.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing MBene materials have small layer spacing, resulting in limited specific surface area, limiting their performance and efficiency in applications.

Method used

By mixing MoAlB with NaOH solution, subjecting to hydrothermal treatment, collecting precipitates and removing impurities, MBene powder was obtained, and then stirred and reacted with the intercalation solution to form an accordion-like wrinkle structure, which significantly increased the specific surface area of ​​the material.

Benefits of technology

It significantly increases the specific surface area of ​​MBene material, provides more edge sites and surfactant sites, improves the performance of the material in catalysis, sensing and other applications, and enhances mechanical properties and structural stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119873851A_ABST
    Figure CN119873851A_ABST
Patent Text Reader

Abstract

The invention discloses an accordion-shaped MBene material and a preparation method thereof, belongs to the technical field of material engineering, and solves the problem that the application efficiency of an MBene material in the prior art is not ideal enough. The method comprises the following steps: stirring and reacting 10-100 parts by mass of MBene powder and 10-100 parts by mass of an intercalation solution at room temperature, collecting a precipitate, and purifying to obtain the accordion-shaped MBene material. According to the accordion-shaped MBene material provided by the invention, morphological structures of the MBene material are stacked into an accordion-shaped wrinkle structure, so that the specific surface area of the material is remarkably increased. The increase of the specific surface area means more edge sites and surface active sites, and the sites can be used as reaction centers to improve the performance of the material in catalysis, sensing and other applications.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of material engineering technology, and more specifically to an accordion-shaped MBene material and a preparation method thereof. Background Art

[0002] MXenes are represented by the standard equation M n+1 X n T x MXenes are two-dimensional transition metal carbides, nitrides, and carbonitrides described by (n=1-4), where M, X, and T represent transition metal materials, carbon / nitrogen, and surface suspensions, respectively. n+1 AX n Synthesized from various tertiary transition metal carbides and nitrides, the atomic structure of which is characterized by M n+1 X n The MAX phase is composed of a series of 2- and 4-H phases, each of which is composed ... n+1 X n Partially, pristine MXenes with sequential atomic configurations of n+1 energy level of M and n energy level of X can be synthesized and maintained in the MAX state. Subsequently, the crystalline layer is eliminated by directional ablation in solution. The chemical bonds in the etchant may terminate the high-energy face of the transition metal, resulting in the generation of external terminals such as O, OH, F, etc. Due to their unique properties and structures, MXenes are applied in many fields, including energy, electronics, catalysis, environmental aspects, etc.

[0003] An innovative form of two-dimensional transition metal boride as an alternative to MXenes, referred to as MBenes, is formed by selective etching of the A layer of a multilayer structure (MAB phase). The MA bond is metallic, while the MB bond exhibits covalent / metal / ionic mixed characteristics. The difference between MBenes and MXenes is that boron replaces the carbon and / or nitrogen sites of MXenes. However, due to changes in stoichiometry and structural transformation, MAB-MBenes cannot be directly connected to the MAX-MXenes combination. MBenes materials show potential advantages in the following aspects: more compact structure and higher mechanical strength, higher electron mobility, better chemical stability, higher catalytic activity and selectivity, and lightweight materials.

[0004] Molybdenum-based materials have Pt-like d-band electronic structures and multiple oxidation states, high electrical conductivity, excellent intermediate adsorption performance, flexibility, strength, optoelectronic properties, etc., making them ideal candidates for sensing, catalysis, energy harvesting, electronics, energy storage, ion transport, superconductivity, and hydrogen storage. Two-dimensional metal borides with covalent networks have also attracted great interest because most of them are metals, have high electrical conductivity, can quickly transfer electrons, and the abundant catalytic active sites guarantee higher electrocatalytic activity than the corresponding systems. As d-block elements with multiple oxidation states, molybdenum-based borides have the characteristics of low cost, easy synthesis, diverse structures, high chemical stability, corrosion resistance, high hardness, and can replace precious metal catalysts. The rich structure of molybdenum borides exhibits interesting chemical and mechanical properties, which are established by the rearrangement and ratio of boron and molybdenum atoms in a single unit cell. Molybdenum-boron-based nanomaterials have both good electrical conductivity and abundant catalytic active sites due to their special crystal structure and the presence of unsaturated edge sites, which are caused by the severe electron deficiency of boron atoms.

[0005] However, due to the small interlayer spacing and relatively limited specific surface area of ​​the MBene material in the prior art, its performance and efficiency in applications are limited. Therefore, the present invention reports a method for preparing an accordion-shaped MBene material, which provides a new approach for the preparation of single-layer MBene. Summary of the invention

[0006] The present invention provides an accordion-shaped MBene material and a preparation method thereof, so as to solve the problem that the application efficiency of the MBene material in the prior art is not ideal.

[0007] In a first aspect, the present invention provides a method for preparing an accordion-shaped MBene material, comprising the following steps: mixing MoAlB with a NaOH solution, reacting at a temperature of 50 to 250° C., collecting a first precipitate and performing a decontamination treatment to obtain MBene powder; mixing 100 to 300 parts by mass of water, 10 to 100 parts by mass of tetraethylammonium hydroxide, 10 to 100 parts by mass of sodium ethylenediaminetetraacetate, 10 to 100 parts by mass of sodium gluconate and 5 to 20 parts by mass of triethanolamine borate, and stirring the mixture evenly at room temperature to obtain an intercalation solution; stirring 10 to 100 parts by mass of the MBene powder and 10 to 100 parts by mass of the intercalation solution at room temperature to react, collecting a second precipitate and performing a purification treatment to obtain the accordion-shaped MBene material.

[0008] As a possible implementation, the concentration of the NaOH solution is 10wt% to 50wt%; and / or, in the preparation of the intercalation solution, the stirring conditions are: a rotation speed of 6000 to 10000 rpm and a duration of 1 to 30 min; and / or, in the preparation of the second precipitate, the stirring reaction conditions are: a rotation speed of 3000 rpm and a duration of 1 to 10 min.

[0009] As a possible implementation method, the impurity removal treatment includes the steps of: washing the first precipitate with a NaOH diluent, then washing with deionized water to a pH of 6 to 8, and freeze-drying to obtain the MBene powder; and / or, the purification treatment includes the steps of: washing the second precipitate with ethanol, then washing with deionized water, and freeze-drying to obtain the accordion-shaped MBene material.

[0010] As a possible implementation manner, the mass ratio of the MBene powder to the intercalation solution is 1:1.

[0011] In a second aspect, the present invention provides an accordion-shaped MBene material prepared by the preparation method described in any possible implementation manner of the first aspect.

[0012] As a possible implementation, it has a significantly larger interlayer spacing.

[0013] In a third aspect, the present invention provides an application of the accordion-shaped MBene material described in any possible implementation of the second aspect in the field of sensing.

[0014] As a possible implementation method, the accordion-shaped MBene material is used as a lightweight material in the catalytic field.

[0015] Traditional MBene materials usually exist in a two-dimensional sheet structure, and their specific surface area is relatively limited; the accordion-shaped MBene material provided by the present invention significantly increases the specific surface area of ​​the material by stacking the morphological structure of the MBene material into an accordion-shaped folded structure. The increase in specific surface area means more edge sites and surface active sites, which can serve as reaction centers to improve the performance of the material in applications such as catalysis and sensing.

[0016] Traditional MBene materials are prone to agglomeration and stacking due to their sheet-like structure, which may lead to decreased mechanical properties and structural instability. The folded structure of the accordion-shaped MBene material provided by the present invention gives the material a spring-like buffering effect, which can absorb and disperse external stress, enhance the material's mechanical properties, mechanical strength and flexibility, and improve its bending and compression resistance; and the folded structure helps prevent the MBene material from agglomerating and stacking, maintains its structural integrity, and thus improves the material's service life.

[0017] The present invention's research on the preparation method of accordion-shaped MBene materials has promoted the innovation and development of related material preparation technologies; by precisely controlling the structural parameters of the materials, the material properties can be customized to meet the needs of different application scenarios. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0019] Figure 1 This is a SEM image of MoAlB provided in an embodiment of the present invention.

[0020] Figure 2 This is a SEM image of the traditional MBene material provided in the embodiment of the present invention.

[0021] Figure 3 This is a SEM image of the accordion-shaped MBene material A provided in an embodiment of the present invention.

[0022] Figure 4 This is a SEM image of the accordion-shaped MBene material B provided in an embodiment of the present invention.

[0023] Figure 5 This is a SEM image of the accordion-shaped MBene material C provided in an embodiment of the present invention. DETAILED DESCRIPTION

[0024] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] In order to solve the problem that the application efficiency of MBene materials in the prior art is not ideal, an embodiment of the present invention provides a preparation and characterization experiment of an accordion-shaped MBene material.

[0026] The preparation experiment includes the steps of mixing MoAlB powder with 10wt% to 50wt% NaOH solution, hydrothermally treating at 50 to 250°C for 24h, collecting the precipitate (first precipitate) after the reaction, washing the obtained precipitate with NaOH diluent, then washing with deionized water to pH 6 to 8, freeze drying, (impurity removal treatment) to obtain MBene powder. In parts by mass, 100 to 300 parts of water, 10 to 100 parts of tetraethylammonium hydroxide, 10 to 100 parts of sodium ethylenediaminetetraacetate, 10 to 100 parts of sodium gluconate, 5 to 20 parts of triethanolamine borate, stirring at room temperature at 6000 to 10000 rpm for 1 to 30 minutes, and obtaining an intercalation solution. In parts by mass, 10 to 100 parts of intercalation solution and 10 to 100 parts of MBene powder are stirred at 3000 rpm at room temperature for 1 to 10 minutes. After the reaction, the precipitate (second precipitate) is collected and washed with ethanol and then with deionized water, and freeze-dried (purified) to obtain an accordion-shaped MBene material.

[0027] Figure 1 The SEM morphology diagram of MoAlB, one of the raw materials for the preparation experiment provided in the embodiment of the present invention, is exemplarily shown.

[0028] The present invention measures the specific surface areas of the accordion-shaped MBene materials and common MBene materials prepared in Examples 1 to 3, and the results show that the accordion-shaped MBene materials prepared in the present invention have significantly higher specific surface areas.

[0029] The accordion-shaped MBene material provided by the present invention significantly increases the specific surface area of ​​the material by stacking the morphological structure of the MBene material into an accordion-shaped folded structure. The increase in specific surface area means more edge sites and surface active sites, which can serve as reaction centers to improve the performance of the material in applications such as catalysis and sensing.

[0030] The technical solution of the present invention will be further described below in conjunction with specific embodiments.

[0031] Example 1

[0032] This embodiment provides a preparation and characterization experiment of an accordion-shaped MBene material.

[0033] MoAlB and NaOH solution were mixed and reacted at a temperature of 50°C, the first precipitate was collected and impurity removal was performed to obtain MBene powder; 300 parts of water, 10 parts of tetraethylammonium hydroxide, 10 parts of sodium ethylenediaminetetraacetate, 10 parts of sodium gluconate and 5 parts of triethanolamine borate were mixed by weight and stirred evenly at room temperature to obtain an intercalation solution; 10 parts of MBene powder and 100 parts of the intercalation solution were stirred and reacted at room temperature, the second precipitate was collected and purified to obtain an accordion-shaped MBene material.

[0034] Example 2

[0035] This embodiment provides a preparation and characterization experiment of an accordion-shaped MBene material.

[0036] MoAlB and NaOH solution are mixed and reacted at a temperature of 250°C, the first precipitate is collected and impurity removal is performed to obtain MBene powder; 100 parts of water, 100 parts of tetraethylammonium hydroxide, 100 parts of sodium ethylenediaminetetraacetate, 100 parts of sodium gluconate and 20 parts of triethanolamine borate are mixed by mass and stirred evenly at room temperature to obtain an intercalation solution; 100 parts of MBene powder and 10 parts of the intercalation solution are stirred and reacted at room temperature, the second precipitate is collected and purified to obtain an accordion-shaped MBene material.

[0037] Example 3

[0038] This embodiment provides a preparation and characterization experiment of an accordion-shaped MBene material.

[0039] MoAlB and NaOH solution are mixed and reacted at a temperature of 150°C, and the first precipitate is collected and subjected to impurity removal treatment to obtain MBene powder; 200 parts of water, 50 parts of tetraethylammonium hydroxide, 50 parts of sodium ethylenediaminetetraacetate, 50 parts of sodium gluconate and 12 parts of triethanolamine borate are mixed by weight and stirred evenly at room temperature to obtain an intercalation solution; 50 parts of MBene powder and 50 parts of intercalation solution are stirred and reacted at room temperature, and the second precipitate is collected and subjected to purification treatment to obtain an accordion-shaped MBene material.

[0040] Example 4

[0041] This embodiment provides a performance characterization experiment of an accordion-shaped MBene material.

[0042] The conventional MBene material was characterized by SEM, and the following results were obtained: Figure 2 Results shown, where the scale bars from top to bottom are 5 μm, 5 μm, and 10 μm, respectively.

[0043] The accordion-shaped MBene materials prepared in Example 1, Example 2 and Example 3 were characterized by SEM, respectively, and the following results were obtained: Figure 3 , Figure 4 and Figure 5 Results shown.

[0044] Depend on Figure 2 Can Figure 3 to Figure 5 From the comparison, it can be seen that the accordion-shaped MBene materials prepared in Examples 1 to 3 of the present invention have significantly larger and more uniform layer gaps. This wrinkled structure significantly increases the specific surface area of ​​the material. The increase in specific surface area means more edge sites and surface active sites, which can serve as reaction centers to improve the performance of the material in applications such as catalysis and sensing.

[0045] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0046] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A method for preparing an accordion-shaped MBene material, characterized in that: The following steps are involved: MoAlB and NaOH solution are mixed, reacted at a temperature of 50 to 250° C., a first precipitate is collected and impurity-removed to obtain MBene powder; In parts by mass, 100 to 300 parts of water, 10 to 100 parts of tetraethylammonium hydroxide, 10 to 100 parts of sodium ethylenediaminetetraacetate, 10 to 100 parts of sodium gluconate and 5 to 20 parts of triethanolamine borate are mixed and stirred uniformly at room temperature to obtain an intercalation solution; In parts by mass, 10 to 100 parts of the MBene powder and 10 to 100 parts of the intercalation solution are stirred and reacted at room temperature, and the second precipitate is collected and purified to obtain the accordion-shaped MBene material.

2. The preparation method according to claim 1, characterized in that: The concentration of the NaOH solution is 10wt% to 50wt%; And / or, in the preparation of the intercalation solution, the stirring conditions are: a rotation speed of 6000 to 10000 rpm and a duration of 1 to 30 min; And / or, in the preparation of the second precipitate, the stirring reaction conditions are: a rotation speed of 3000 rpm and a duration of 1 to 10 min.

3. The preparation method according to claim 1, characterized in that: The impurity removal treatment comprises the steps of: washing the first precipitate with a NaOH diluent, then washing with deionized water until the pH is 6 to 8, and freeze-drying to obtain the MBene powder; And / or, the purification process comprises the steps of: washing the second precipitate with ethanol, then washing with deionized water, and freeze-drying to obtain the accordion-shaped MBene material.

4. The preparation method according to claim 1, characterized in that: The mass ratio of the MBene powder to the intercalation solution is 1:

1.

5. The accordion-shaped MBene material prepared by the preparation method according to any one of claims 1 to 4.

6. The accordion-shaped MBene material according to claim 5, characterized in that: It has a significantly larger interlayer spacing.

7. Use of the accordion-shaped MBene material according to any one of claims 5 to 6 in the field of catalysis.

8. The use according to claim 7, characterized in that: The accordion-shaped MBene material is used as a lightweight material in the catalytic field.